The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1550-2783-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hydration status of elite Olympic class sailors in different climates and the effects of different fluid replacement beverages

Abstract: BackgroundOlympic class sailing poses physiological challenges similar to other endurance sports such as cycling or running, with sport specific challenges of limited access to nutrition and hydration during competition. As changes in hydration status can impair sports performance, examining fluid consumption patterns and fluid/electrolyte requirements of Olympic class sailors is necessary to develop specific recommendations for these elite athletes. The purpose of this study was to examine if Olympic class sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 41 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…Both supplements are important for the replenishment of nutrients and hydration during competition periods, providing energy and nutrients when it is not practical to consume daily foods due to the limitation of the boat in the case of the bars, and seeking to counteract the high sweating rates generated by the typical weather conditions of this sport in the case of sports drinks [41,42]. In addition, the use of these two SS can prevent the deterioration of endurance, strength, blood volume, and cognitive function during competition [43]. It should also be added that, among the most consumed SS, caffeine and dextrose also stand out, which are also often used during competition [1,44].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both supplements are important for the replenishment of nutrients and hydration during competition periods, providing energy and nutrients when it is not practical to consume daily foods due to the limitation of the boat in the case of the bars, and seeking to counteract the high sweating rates generated by the typical weather conditions of this sport in the case of sports drinks [41,42]. In addition, the use of these two SS can prevent the deterioration of endurance, strength, blood volume, and cognitive function during competition [43]. It should also be added that, among the most consumed SS, caffeine and dextrose also stand out, which are also often used during competition [1,44].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the characteristics of the competitions, the boats, and the weather conditions in dinghy sailing can also lead to the inclusion of supplements of the sports foods category of Group A, such as drinks and sports gels, sports bars, liquid foods or whey protein. The inclusion of sports drinks is essential to restore the sailor's hydroelectrolytic balance [65] and, thus, to alleviate one of the most frequent problems during sailing competitions, i.e., dehydration, and the consequent deterioration of performance and health of the sailor [16][17][18]43]. In addition, these drinks should include carbohydrates, which, added to their electrolytes, prevent the deterioration of endurance, strength, blood volume, and cognitive function in competitions of this duration [43,66].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Slater and Tan reported dehydration greater than 2% of body weight in sailors, potentially leading to performance decrements (Slater & Tan, 2007). Lewis et al reported significant body mass losses in competitive sailors even in cold conditions despite ad libitum fluid intake (Lewis, Fraser, Thomas, & Wells, 2013). The current investigation shows similar results for hydration status when observed separately each day of the competition.…”
Section: Discussionmentioning
confidence: 99%